Multiplex Networks to Characterize Seizure Development in Traumatic Brain Injury Patients - La Rocca, Marianna; Garner, Rachael; Amoroso, Nicola; Lutkenhoff, Evan S.; Monti, Martin M.; Vespa, Paul; Toga, Arthur W.; Duncan, Dominique (Frontiers in Neuroscience, 2020)
Traumatic brain injury (TBI) may cause secondary debilitating problems, such as post-traumatic epilepsy (PTE), which occurs with unprovoked recurrent seizures, months or even years after TBI. Currently, the Epilepsy Bioinformatics Study for Antiepileptogenic Therapy (EpiBioS4Rx) has been enrolling moderate-severe TBI patients with the goal to identify biomarkers of epileptogenesis that may help to prevent seizure occurrence and better understand the mechanism underlying PTE. In this work, we used a novel complex network approach based on segmenting T1-weighted Magnetic Resonance Imaging (MRI) scans in patches of the same dimension (network nodes) and measured pairwise patch similarities using Pearson's correlation (network connections). This network model allowed us to obtain a series of single and multiplex network metrics to comprehensively analyze the different interactions between brain components and capture structural MRI alterations related to seizure development. We used these complex network features to train a Random Forest (RF) classifier and predict, with an accuracy of 70 % and a 95% confidence interval of [67%,73%], which subjects from EpiBioS4Rx have had at least one seizure after a TBI. This complex network approach also allowed the identification of the most informative scales and brain areas for the discrimination between the two clinical groups: seizure-free and seizure-affected subjects, bluedemonstrating to be a promising pilot study which, in the future, may serve to identify and validate biomarkers of PTE.